Primary hepatic tuberculosis presenting as fever of unknown origin diagnosed by Positron emission tomography/computed tomography scan (PET/CT) - Saurabh Puri; Ashok Grover; Pankaj Nand Choudhary; Purneetha Singh; Arjun Prem Gupta (Journal of Family Medicine and Primary Care, 2022)
Tuberculosis (TB), especially extrapulmonary tuberculosis (EPTB), is an important cause of fever of unknown origin (FUO) in areas endemic to TB. Liver involvement in TB in the absence of miliary TB is rare. A definitive diagnosis of primary hepatic TB can be challenging and relies on the histological and/or bacteriological findings of the liver tissue obtained by biopsy. TB should be considered in the differential diagnosis of space-occupying lesions and abscesses of the liver. In our case of a 52-year-old adult male with FUO, a positron emission tomography/computed tomography (PET/CT) scan was used, due to lack of any potential diagnostic clues, and a focal lesion was identified as a potential biopsy site.